Field Operations Guide for Disaster Assessment and Response (Skyhorse Publishing, Inc., 2013)
In developing this third revision of version 4.0 of the Field Operations Guide for Disaster Assessment and Response, the Office of U.S. Foreign Disaster Assistance (OFDA) of the United States Agency of International Development (USAID) has drawn on the expertise of numerous state, national, and international agencies and organizations. Selected sources of information include the United Nations High Commissioner for Refugees' Handbook for Emergencies, the United Nations Office for the Coordination of Humanitarian Affairs' United Nations Disaster Assessment and Coordination Field Handbook, and the U.S. Public Health Service's Handbook of Environmental Health, among others.